Analisa Penerapan Sistem Enterprise Resource Planning dan Manajemen Rantai Pasokan Pada PT Semen Padang Dalam Meningkatkan Kinerja Perusahaan - Rizky Adi Mahendra; Inda Meyllya Putri; Michael Iken Bonar Anju Sibagariang; Nabila Arinov Mey; Pradino Kusumo; Rince Monica Hutagalung; Wisnu Yuwono; Fitriana Aidnilla Sinambela (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
This study aims to analyze the application of enterprise resource planning and supply chain management systems from PT Semen Padang in improving company performance. Analyzing the obstacles experienced by PT Semen Padang in implementing the ERP system in its business processes. The research method applied in this study is a qualitative method and Secondary Data Analysis (ADS), namely using and analyzing existing data without having to conduct surveys and interviews. The results obtained from this study are that there is an increase in the performance of the company's supply chain by implementing the Enterprise Resource Planning (ERP) system as evidenced by an increase in the amount of cement production in the following year.